Microwave synthesis of new 3-(alkylthio)-5-(thiophen2-ylmethyl)-1,2,4-triazol-4-amines - Safonov, A.; Сафонов, Андрій Андрійович (My University, 2020)
The aim of this work is to synthesize 3-(alkylthio)-5-(thiophen-2-ylmethyl)-1,2,4-triazol-4- amines by the Milestone Flexi Wave microwave synthesis system and to prove structure synthesized compounds.
Keywords: 1,2,4-triazole; synthesis; 1 H-NMR; gas chromatography; heterocyclic compounds